2017
DOI: 10.1016/j.diabres.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Circulating early- and mid-pregnancy microRNAs and risk of gestational diabetes

Abstract: Aims Epigenetic regulators, including microRNAs(miRNAs), are implicated in type 2 diabetes, but evidence linking circulating miRNAs in pregnancy and risk of gestational diabetes(GDM) is sparse. Potential modifiers, including pre-pregnancy overweight/obesity and offspring sex, are unexamined. We hypothesized that circulating levels of early-mid-pregnancy(range 7-23 weeks of gestation) candidate miRNAs are related to subsequent development of GDM. We also hypothesized that miRNA-GDM associations might vary by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 69 publications
0
123
1
3
Order By: Relevance
“…However, most of microRNAs, which were the subjects of our interest, have not yet been observed by other investigators to be dysregulated in maternal circulation (peripheral blood, plasma, or serum samples) of women with clinically established GDM or before the onset of GDM [20,21,37,80,92,143,149,[172][173][174][175][176]. So, it is feasible that epigenetic profiles of a series of microRNAs have also been changing with time by force of various circumstances as a result of the interaction between genetic and environmental factors [177].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, most of microRNAs, which were the subjects of our interest, have not yet been observed by other investigators to be dysregulated in maternal circulation (peripheral blood, plasma, or serum samples) of women with clinically established GDM or before the onset of GDM [20,21,37,80,92,143,149,[172][173][174][175][176]. So, it is feasible that epigenetic profiles of a series of microRNAs have also been changing with time by force of various circumstances as a result of the interaction between genetic and environmental factors [177].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, a set of circulating microRNAs associated with cardiovascular/cerebrovascular diseases (miR-16-5p, miR-17-5p, miR-20a-5p, miR-29a-3p, miR-125b-5p, and miR-195-5p) was reported by several independent studies [20,21,80,92,143,172,173] to be upregulated during various gestational ages in serum or plasma of mothers with already-diagnosed GDM or mothers who were destined to develop GDM later during pregnancy. The data resulting from these prenatally ongoing studies and interaction network analysis [20,21,80,92,98,125,143,172,173] may support our current finding referring to upregulated expression profile of these particular microRNAs in whole peripheral blood of women with a prior exposure to GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Wander et al. (), which included 116 women, revealed that miR‐155‐5p and miR‐21‐3p plasma levels in the early stages of pregnancy are connected with higher risk of GDM. The miRNAs miR‐21‐3p and miR‐210‐3p also showed association with GDM, but only in overweight women.…”
Section: Epigenetics Of Gdmmentioning
confidence: 99%
“…31,32 MiR-210-3p has been previously shown to be involved in adipogenesis, is differentially expressed in visceral adipose tissues in obese T2DM individuals, and is associated with gestational diabetes in obese women. [33][34][35][36] Using validated miRNA targets, we explored the possible biological processes/pathways that might be affected by the dysregulated miRNAs. A number of signal transduction related processes that play important roles in T2DM pathophysiology, including the insulin signaling pathway, mTOR signaling pathway, TGF-β signaling pathway, and VEGF signaling pathway [37][38][39][40] were enriched in this analysis.…”
Section: Log 2 Fc (> 15 Fold Change P-value B-h Fdrmentioning
confidence: 99%